Advances in arterial-derived immune cells invascular homeostasis and disease - Liu Henan; Li Dan; Li Jingyong; Cheng Xiang (生物医学转化, 2021)
A variety of immune cells are widely distributed in organs and tissues of the body, participating in the mediation of innate and adaptive immune responses, and playing an important role in tissue growth and development, tissue repair and homeostasis maintenance. Recent years, with the introduction of the concept of tissue specificity, researchers began to study the functional characteristics of different immune cells in different tissues.Focusing on immune cells in the arterial system, we introduces the research status of immune cells such as T cells,B cells, macrophages and dendritic cells in vascular homeostasis and common vascular diseases，in order to provide theoretical basis for targeting arterial immune response and reducing the incidence of vascular diseases.